Conducting Community Audits to Evaluate Community Resources for Healthful Lifestyle Behaviors: An Illustration From Rural Eastern North Carolina - McGuirt, Jared T. (Centers for Disease Control and Prevention, 2011)
A community audit is a qualitative and quantitative research technique in which researchers drive through a community to observe its physical and social attributes, primarily through windshield tours and "ground truthing." Ground truthing is a verification process that uses data gathered by direct observation to corroborate data gathered from secondary sources. Community audits have been used for epidemiologic studies and in program planning for health-promotion interventions. Few studies have detailed the methodology for conducting community audits in rural areas or the extent to which community audits can contribute to an accurate assessment of community characteristics (eg, presence of sidewalks) and nutrition and physical activity resources (eg, produce stands, parks) that may promote healthful lifestyle behaviors. The objective of this article is to describe our approach to conducting a community audit (consisting of windshield tours and ground truthing) to enumerate resources, to assess community characteristics, and to inform revisions to a community guide on nutrition and physical activity resources. We conducted an audit in 10 communities in a rural eastern North Carolina county in 2010. We also collected data from secondary sources to make comparisons with community audit data. The initial resource guide included 42 resources; the community audits identified 38 additional resources. There was moderate to high agreement between windshield tour observations and secondary data sources for several community characteristics, such as number of fast-food restaurants (67% agreement) and existence of sidewalks (100% agreement). Community audits improved the description of health-promoting community resources and the context in which people make lifestyle choices.